Proceedings of the 2018 Conference of the North American Chapter Of the Association for Computational Linguistics: Hu 2018
DOI: 10.18653/v1/n18-1035
|View full text |Cite
|
Sign up to set email alerts
|

Microblog Conversation Recommendation via Joint Modeling of Topics and Discourse

Abstract: Millions of conversations are generated every day on social media platforms. With limited attention, it is challenging for users to select which discussions they would like to participate in. Here we propose a new method for microblog conversation recommendation. While much prior work has focused on postlevel recommendation, we exploit both the conversational context, and user content and behavior preferences. We propose a statistical model that jointly captures: (1) topics for representing user interests and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 42 publications
(34 reference statements)
2
45
0
Order By: Relevance
“…Topic Models. Well-known topic models, e.g., probabilistic latent semantic analysis (pLSA) (Hofmann, 1999) and latent Dirichlet allocation (LDA) (Blei et al, 2003), have shown advantages in capturing effective semantic representations, and proven beneficial to varying downstream applications, such as summarization (Haghighi and Vanderwende, 2009) and recommendation (Zeng et al, 2018;Bai et al, 2018). For short text data, topic model variants have been proposed to reduce the effects of sparsity issues on topic modeling, such as biterm topic model (BTM) (Yan et al, 2013) and LeadLDA (Li et al, 2016b).…”
Section: Related Workmentioning
confidence: 99%
“…Topic Models. Well-known topic models, e.g., probabilistic latent semantic analysis (pLSA) (Hofmann, 1999) and latent Dirichlet allocation (LDA) (Blei et al, 2003), have shown advantages in capturing effective semantic representations, and proven beneficial to varying downstream applications, such as summarization (Haghighi and Vanderwende, 2009) and recommendation (Zeng et al, 2018;Bai et al, 2018). For short text data, topic model variants have been proposed to reduce the effects of sparsity issues on topic modeling, such as biterm topic model (BTM) (Yan et al, 2013) and LeadLDA (Li et al, 2016b).…”
Section: Related Workmentioning
confidence: 99%
“…Both data sets were collected from Twitter. The Election-Trec data set is constructed based on the TREC2011 microblog track 1 and the Election data set 2 shared by Zeng et al (2018). For the TREC2011 data set, to recover conversations, we used the tweet search API 3 to retrieve full information of a tweet with its "in reply to status id" included.…”
Section: Data Collectionmentioning
confidence: 99%
“…In previous studies, it has been shown that effective online conversation recommendation has the potential to produce more positive online social interaction experience (Chen et al, 2011;Zeng et al, 2018). Prior work on this subject has focused on post-level recommendation (Yan et al, 2012;Chen et al, 2012), or conversation-level suggestion with handcrafted features (Chen et al, 2011) and word co-occurrence patterns (Zeng et al, 2018). Nevertheless, they ignore the useful information embedded in replying relations, where the conversation structure is formed via messages sent among users.…”
Section: Introductionmentioning
confidence: 99%
“…We then incorporate the interaction representations into a novel neural collaborative filtering framework (He et al, 2017), which further aligns user's preferences with the conversation context. Compared with existing methods that are based on handcrafted features (Chen et al, 2011) or Bayesian models (Zeng et al, 2018), our end-toend trained neural model learns to automatically recommend conversations as well as to encode user interests embedded in their conversation interactions. To the best of our knowledge, this is the first work to explore neural conversation recommendation with online interactions explicitly encoded for user preference modeling.…”
Section: Introductionmentioning
confidence: 99%